2022
DOI: 10.3390/v14102197
|View full text |Cite
|
Sign up to set email alerts
|

Association of Midgut Bacteria and Their Metabolic Pathways with Zika Infection and Insecticide Resistance in Colombian Aedes aegypti Populations

Abstract: Introduction: Aedes aegypti is the vector of several arboviruses such as dengue, Zika, and chikungunya. In 2015–16, Zika virus (ZIKV) had an outbreak in South America associated with prenatal microcephaly and Guillain-Barré syndrome. This mosquito's viral transmission is influenced by microbiota abundance and diversity and its interactions with the vector. The conditions of cocirculation of these three arboviruses, failure in vector control due to insecticide resistance, limitations in dengue management during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 145 publications
0
5
0
Order By: Relevance
“…However, the bacterial community undergoes dynamic changes throughout the life cycle of mosquitoes, with composition variations based on factors such as mosquito gender, developmental stage, and ecological conditions 42 . Therefore, these variations in microbiota composition may help elucidate the vector competence commonly observed across mosquito populations 43 . Additionally, microbiota can influence mosquito development 19 , nutrient acquisition 44 , blood digestion 45 , and the synthesis of the peritrophic matrix 46 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the bacterial community undergoes dynamic changes throughout the life cycle of mosquitoes, with composition variations based on factors such as mosquito gender, developmental stage, and ecological conditions 42 . Therefore, these variations in microbiota composition may help elucidate the vector competence commonly observed across mosquito populations 43 . Additionally, microbiota can influence mosquito development 19 , nutrient acquisition 44 , blood digestion 45 , and the synthesis of the peritrophic matrix 46 .…”
Section: Discussionmentioning
confidence: 99%
“…aegypti , blood-derived heme induces iron- and ROS-dependent signaling that also regulates immune genes, affecting DENV susceptibility (85). Metabolism of Bacteroides associates with elevated ZIKV susceptibility and conditions insecticide resistance (86), implicating a complex metabolic network that can also influence arbovirus susceptibility. Further investigation of the relationship between blood digestion and immunity could uncover novel determinants of mosquito vector competence.…”
Section: Discussionmentioning
confidence: 99%
“…increase AMPs production by activating the Toll pathway, thus reducing DENV infection ( Figure 2A -VI), and Beauveria bassiana fungus in A. aegypti activates the JAK-STAT and Toll pathways, thereby increasing resistance to DENV (Dong et al, 2012 ). In contrast, DENV can induce AMPs production to reduce gut microbiota (Ramirez et al, 2012 ), ZIKV has also been reported to modulate microbiota composition (Arévalo-Cortés et al, 2022 ). Microbiota bacteria also affect the development of Serratia (Kozlova et al, 2021 ).…”
Section: Mosquitoes and Arbovirusmentioning
confidence: 99%